2015
DOI: 10.1039/c5tx00210a
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic mechanisms of disulfiram and copper(ii) in cancer cells

Abstract: The anticancer activity of disulfiram (DS) is copper(ii) (Cu)-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 21 publications
2
74
0
Order By: Relevance
“…DS is highly cytotoxic in several types of cancer cells in vitro ,6, 10, 15, 16, 30, 31, 32 whereas oral administration of free DS does not inhibit tumor growth in vivo 33 . Recent publication suggests that the intact sulfhydryl group is essential for the anticancer function of DS 22, 24. The degradation of DS in the bloodstream destroys the sulfhydryl group making DS lose its cancer targeting ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DS is highly cytotoxic in several types of cancer cells in vitro ,6, 10, 15, 16, 30, 31, 32 whereas oral administration of free DS does not inhibit tumor growth in vivo 33 . Recent publication suggests that the intact sulfhydryl group is essential for the anticancer function of DS 22, 24. The degradation of DS in the bloodstream destroys the sulfhydryl group making DS lose its cancer targeting ability.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of DS is copper (Cu), zinc and some other divalent transitional metal elements dependent 11, 20, 21, 22. DS is quickly reduced to diethyldithiocarbamate (DDC), a strong chelator of copper(II).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously Tawari et al noted an increase in ROS when DSF and copper were added to cell media but not when DDC and copper were added. 20 The authors suggested that ROS generation was a by-product produced that occurred when DSF and Cu were mixed in vitro. However, ROS would not be generated if using preformed Cu(DDC) 2 complex in liposomes, as done in the studies reported here.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests clearly that the copper complex of DDC is the therapeutically active agent. 19,20 Cvek et al have shown that Cu(DDC) 2 acts as a proteosome inhibitor, 21 specifically through binding to the 19S lid of the proteosome rather than the 20S subunit, which is targeted by bortezomib. 22 Before developing any therapeutic application for Cu(DDC) 2 , there are formulation issues that need to be addressed if its use in vivo is to be evaluated.…”
Section: Introductionmentioning
confidence: 99%